The Development of Western music. CD#6: an anthology - Sony Music Entertainment (New York : McGraw-Hill.)
"Specifically designed to present music to be studied in conjunction with the text The development of Western music : a history"--Pref.
Volume 2. Preclassic through the twentieth century.
Keywords: Musical analysis -- Music collections; Wester music